Cost-effectiveness analysis of routine 13-valent pneumococcal conjugate vaccinations in Chinese infants. Issue 6 (3rd June 2018) - Zhou, Hua; He, Jinchun; Wu, Bin; Che, Datian
ABSTRACT: Background: This study aimed to evaluate the cost-effectiveness of the 13-valent pneumococcal conjugate vaccine (PCV-13) compared to a no vaccination strategy in Chinese infants. Methods: A Markov process model was developed to examine the outcomes of PCV-13 against a no vaccination strategy using data and assumptions adapted for relevance to China. Outcomes over a lifetime horizon are presented. One-way and probabilistic sensitivity analyses were performed to determine the uncertainty. Results: Compared to no vaccination, a PCV-13 vaccination program would provide a gain of 0.009 additional quality-adjusted life years (QALYs) per subject. From the health care and societal perspectives, the incremental costs per QALY were 20, 709 and 18, 483, respectively. When herd effect was included, the cost effectiveness of the PCV-13 vaccination strategy was notably improved. The lower price of PCV-13 will improve the cost-effectiveness. Conclusions: The PCV-13 vaccination is likely to be cost-effective at the current Chinese prices and ceiling threshold (8, 382).